Geometrical optimization and contact configuration in radial pn junction silicon nanorod and microrod solar cells. (13th June 2012) - Voigt, F.; Stelzner, T.; Christiansen, S.
ABSTRACT Electric charge transport simulations of symmetrically doped radial pn junction silicon nanorod solar cells were performed using the Technology Computer‐aided Design software suite by Silvaco. Two schemes of electric contacting were applied, the first one consisting of a cathode wrapped around the cladding of the rod and the second one in a cathode located only on the top rod surface. In both cases, the anode was implemented just below the bottom end of the p‐type rod core. P‐type cores and n‐type shells of the rods were assumed, with dopant densities of 1018 cm− 3 in both regions. The location of the pn junction was chosen such that well‐formed space charge regions could be established with the outer end of the n‐type depletion region being adjacent to the cylindric surface of the nanorod. Rod radii and rod lengths were varied and optimized in a three‐step process for both types of contacting schemes. It was found that inhomogeneous carrier generation profiles diminish the open‐circuit voltage in case of a wrapped cathode configuration. Most realistic is the usage of a top contact configuration with rod radii of 2 µm and lengths of around 100 µm, leading to a cell efficiency of about 15%. Further enhancement of performance is expected, if light trapping of the nanorod layer is taken into account and photonic light harvesting is applied. Copyright © 2012 John Wiley & Sons, Ltd.